Single point mutations in ATP synthase compensate for mitochondrial genome loss in trypanosomes - Dean, S; Gould, MK; Dewar, CE; Schnaufer, AC (National Academy of Sciences, 2013)
Viability of the tsetse fly-transmitted African trypanosome Trypanosoma brucei depends on maintenance and expression of its kinetoplast (kDNA), the mitochondrial genome of this parasite and a putative target for veterinary and human antitrypanosomatid drugs. However, the closely related animal pathogens T. evansi and T. equiperdum are transmitted independently of tsetse flies and survive without a functional kinetoplast for reasons that have remained unclear. Here, we provide definitive evidence that single amino acid changes in the nuclearly encoded F1FO–ATPase subunit γ can compensate for complete physical loss of kDNA in these parasites. Our results provide insight into the molecular mechanism of compensation for kDNA loss by showing FO-independent generation of the mitochondrial membrane potential with increased dependence on the ADP/ATP carrier. Our findings also suggest that, in the pathogenic bloodstream stage of T. brucei, the huge and energetically demanding apparatus required for kDNA maintenance and expression serves the production of a single F1FO–ATPase subunit. These results have important implications for drug discovery and our understanding of the evolution of these parasites.